2005
DOI: 10.1007/s10201-005-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dissolved organic carbon and dissolved fulvic acid in mesotrophic Lake Biwa, Japan

Abstract: The dissolved organic carbon (DOC) concentrations in mesotrophic Lake Biwa were determined by a total organic carbon (TOC) analyzer, and DOC molecular size distributions were determined by size exclusion chromatography (SEC) using a fluorescence detector at excitation/ emission (Ex/Em) levels of 300/425 nm with the eluent at pH 9.7. The fluorescence wavelengths for detection were chosen from the result of excitation-emission matrix spectrometry (EEM) analysis for dissolved fulvic acid (DFA) extracted from Ado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 38 publications
(45 reference statements)
2
9
0
Order By: Relevance
“…Percentages of FAs in the AHS of Lake Biwa in this study tended to increase from spring to winter, and the concentrations of FAs were least in summer. This agrees with the result of Sugiyama et al (2005). In this study, we were able to obtain samples with FA amounts that were adequate for several analyses by using a large-scale preparative isolation apparatus, which enabled the verification of seasonal and qualitative changes in Lake Biwa FAs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Percentages of FAs in the AHS of Lake Biwa in this study tended to increase from spring to winter, and the concentrations of FAs were least in summer. This agrees with the result of Sugiyama et al (2005). In this study, we were able to obtain samples with FA amounts that were adequate for several analyses by using a large-scale preparative isolation apparatus, which enabled the verification of seasonal and qualitative changes in Lake Biwa FAs.…”
Section: Discussionsupporting
confidence: 87%
“…However, there is a little information on the characteristics of FAs isolated from clear water, and reports on the changes in their chemical properties with the season or because of any other factor are rare. Imai et al (1998), Aoki et al (2004) and Sugiyama et al (2005) investigated quantitative changes in AHS (FA) concentrations in Lake Biwa, but they did not examine the qualitative changes in detail. Percentages of FAs in the AHS of Lake Biwa in this study tended to increase from spring to winter, and the concentrations of FAs were least in summer.…”
Section: Discussionmentioning
confidence: 99%
“…The LBFA was prepared following the standard methods used for the isolation of FA standards by International Humic Substances Society (Fujitake et al 2009). The LBFA is a suitable reference material for the clear-water lakes and was chosen instead of humic acid for the purpose of comparison with similar studies and also because FAs are the main component of humic substances in Lake Biwa and in marine systems (Thurman 1985;Sugiyama et al 2005;Fujitake et al 2009). The LBFA was dissolved in ultrapure water and fluorescence spectra were determined similarly to the sample spectra and normalized to QS.…”
Section: Methodsmentioning
confidence: 99%
“…Despite some preliminary studies on the spatial and temporal variation of FDOM (Wu et al 2003;Mostafa et al 2005;Sugiyama et al 2005), a quantitative evaluation on the relationship between DOM productions, organic mineralization, and FDOM dynamics has not been attempted for Lake Biwa. In the present study, using monthly profiles of FDOM in relation to the biogeochemical structure of Lake Biwa, we discuss the coupling between FDOM and biogeochemical processes and explore the tracer-like qualities of FDOM in diagnosing accumulation and mineralization of organic matter in large freshwater lakes.…”
mentioning
confidence: 99%
“…Sugiyama et al (2005) investigated the distribution of DOM and AHSs in a mesotrophic lake at different depths and in different seasons and reported that AHSs accounted for 15.2-40.7 % of DOM. Chanudet and Filella (2007), mentioned in the Introduction, measured the AHS and DOM concentrations in an ultraoligotrophic lake and reported that AHS proportions varied widely, from 11 to 46 %, depending on both the sampling depth and season.…”
Section: Discussionmentioning
confidence: 99%